Income Inequality between Chinese Regions: Newfound Harmony or Continued Discord? - Johan Lyhagen; Johanna Rickne (Research Institute of Industrial Economics (IFN), 2011)
This paper develops an improved test of economic convergence or divergence using time series methods. The usefulness of the method is illustrated in an analysis of the growth pattern between Chinese regions in 19522007. Comparing all combinations of regional pairs, the analysis yields support for economic divergence in roughly half of the cases. In the other half, we instead find that regions have grown while maintaining stable income differences. As such, the results show the co-existence of divergence and conditional convergence among China's regions.
Keywords: C32; O53; R11; 330; China; Output convergence; Non-linear cointegration; Regionales Wachstum; Entwicklungskonvergenz; Regionale Einkommensverteilung; Zeitreihenanalyse; China